A criteria-directed protocol for in-hospital triage of trauma patients. (February 2018) - Granström, Anna; Strömmer, Lovisa; Schandl, Anna; Östlund, Anders
Abstract : Objective: To better match hospital resources to patients' needs of trauma care, a protocol for facilitating in-hospital triage decisions was implemented at a Swedish level I trauma centre. In the protocol, physiological parameters, anatomical injuries and mechanism of injury were documented, and used to activate full or limited trauma team response. The aim of this study was to evaluate the efficacy of the criteria-directed protocol to determine in-hospital trauma triage in an emergency department. Methods: Level of triage and triage rates were compared before and after implementation of the protocol. Overtriage and undertriage were assessed with injury severity score higher than 15 as the cutoff for defining major trauma. Medical records for undertriaged patients were retrospectively reviewed. Results: In 2011, 78% of 1408 trauma team activations required full trauma response, with an overtriage rate of 74% and an undertriage rate of 7%. In 2013, after protocol implementation, 58% of 1466 trauma team activations required full trauma response. Overtriage was reduced to 52% and undertriage was increased to 10%. However, there were no preventable deaths in the undertriaged patients. Conclusion: A criteria-directed protocol for use in the emergency department was efficient in reducing overtriage rates without risking undertriaged patients' safety.